'Did Not Finish': A Phenomenology of Failure. Issue 1 (2nd January 2021) - Gorichanaz, Tim
ABSTRACT: This paper explores what it means to fail in an ultramarathon—be marked DNF, or Did Not Finish—through hermeneutic phenomenology. In today's popular culture, failure holds a paradoxical position: Particularly in the 'startup' ethos, failure is touted as a good, but only because it brings one closer to success. On a Heideggerian perspective, this is an inauthentic understanding of failure. This paper proposes that sport, and specifically ultrarunning, is a site for an authentic understanding of failure—and, consonantly, success. The notion of death is a major consideration: Though death is often described as a kind of failure, it is better understood phenomenologically as that which reveals and focuses one's authentic possibilities for success. Failure, on the other hand, is a cutting-off of possibility. Three types of DNF can be discerned, corresponding to a cutting-off in the past, present and future, respectively. In ultrarunning, an athlete exists as being-toward-death, and finishing belongs to the athlete as part of their self and world. When a DNF happens, an athlete is suddenly rendered incomplete, worldless. This is a jarring, painful experience, from which it takes time and effort, and a reconstruction of self, to recover.